Learning English in Multicultural Contexts: Experiences and Strategies of Secondary Level Students in Rural Nepal - Khanal, Govinda Prasad (Journal of NELTA Gandaki, 2024)
How an additional language can be learned effectively has become an issue of interest among scholars of second language acquisition research. This research intended to explore secondary-level students’ experiences and strategies for learning English in multicultural contexts of classrooms and communities. This is qualitative interpretive research based on a case study design, where five cases from different cultural groups were purposively selected from the students of Grade 11 studying at two different secondary schools in Kapilvastu. The information was collected through semi-structured interviews and classroom observation, which was thematically analysed to report the findings. The study findings revealed that students generated self-learning strategies to fit their situations which tended to be influenced by their socio-cultural and economic realities. Based on the research findings, it is suggested for the adoption of culturally informed pedagogy to value students’ socio-cultural realities including the local languages in practice which provide useful learning resources to enhance proficiency in English.